SERS Quantification of Galunisertib Delivery in Colorectal Cancer Cells by Plasmonic‐Assisted Diatomite Nanoparticles. Issue 34 (24th July 2021) - Managò, Stefano; Tramontano, Chiara; Delle Cave, Donatella; Chianese, Giovanna; Zito, Gianluigi; De Stefano, Luca; Terracciano, Monica; Lonardo, Enza; De Luca, Anna Chiara; Rea, Ilaria
Abstract: The small molecule Galunisertib (LY2157299, LY) shows multiple anticancer activities blocking the transforming growth factor‐β1 receptor, responsible for the epithelial‐to‐mesenchymal transition (EMT) by which colorectal cancer (CRC) cells acquire migratory and metastatic capacities. However, frequent dosing of LY can produce highly toxic metabolites. Alternative strategies to reduce drug side effects can rely on nanoscale drug delivery systems that have led to a medical revolution in the treatment of cancer, improving drug efficacy and lowering drug toxicity. Here, a hybrid nanosystem (DNP‐AuNPs‐LY@Gel) made of a porous diatomite nanoparticle decorated with plasmonic gold nanoparticles, in which LY is retained by a gelatin shell, is proposed. The multifunctional capability of the nanosystem is demonstrated by investigating the efficient LY delivery, the enhanced EMT reversion in CRCs and the intracellular quantification of drug release with a sub‐femtogram resolution by surface‐enhanced Raman spectroscopy (SERS). The LY release trigger is the pH sensitivity of the gelatin shell to the CRC acidic microenvironment. The drug release is real‐time monitored at single‐cell level by analyzing the SERS signals of LY in CRC cells. The higher efficiency of LY delivered by the DNP‐AuNPs‐LY@Gel complex paves the way to an alternative strategy for lowering drug dosing and consequent side effects. Abstract : Galunisertib (LY2157299, LY), a small molecule with anticancer activity, is loaded inside a multifunctional nanosystem made of porous biosilica covered by plasmonic nanoparticles and capped by gelatin. The pH‐triggered‐LY release inducing MET in colorectal cancer (CRC) cells is monitored and quantified with sub‐femtogram resolution by SERS.